Solutions of the Cahn-Hilliard equation - Ugurlu, Yavuz; Kaya, Dogan (Pergamon-Elsevier Science Ltd, 2008)
In this paper, we found some exact solutions of the Cahn-Hilliard equation and the system of the equations by considering a modified extended tanh function method. A numerical solution to a Cahn-Hilliard equation is obtained using a homotopy perturbation method (HPM) combined with the Adomian decomposition method (ADM). The comparisons are given in the tables. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: The Cahn-Hilliard equation; Tanh method; Homotopy perturbation method; The Adomian decomposition method